The European venture capital landscape: an EIF perspective. Volume III: Liquidity events and returns of EIF-backed VC investments - Dario Prencipe (European Investment Fund (EIF), 2017)
Despite the sometimes intensive media coverage and exuberant storytelling around the industry, venture capital (VC) investors tend to operate in highly opaque markets. On this premise, this work contributes to the literature via a hand-collected dataset of about 3,600 EIF-backed VC investments made in the 1996-2015 period, with the aim to analyse their liquidity events and returns. The paper finds, inter alia, that VC returns show sensitivity to the economic cycle. At the same time, it discusses how their heterogeneity leaves room for VC firms to pursue diversification strategies and minimise the correlation with other asset classes. Moreover, this work provides preliminary evidence in support of the often claimed heuristic that VC returns follow a power-law. Finally, it employs competing risks models to analyse time-to-outcome data, observing that VC firm experience only relates positively to performance when outstanding (e.g. 3rd generation fund or above). However, this may also be a reflection of EIF's high-standard screening of first-time VC teams. The paper is structured as follows. Section 1 introduces the key research motivations, while section 2 discusses the features of the analysed dataset. Section 3 provides a descriptive overview of the data, while section 4 discusses the statistical test of power-law behaviour. Section 5 explores exit outcomes against the background of profitable or unprofitable trade sales. Last, section 6 analyses the determinants of exit outcomes. Section 7 concludes.
Keywords: G11; G24; L11; M13; 330; EIF; venture capital; performance; fat tails; divestment; IPO; competing risk analysis